Sources and distribution of tetraether lipids in sediments from the Zhejiang–Fujian coastal mud area, China, over the past 160?years: Implications for paleoclimate change - Chen, L.; Liu, Jian; Wang, J.; Xu, G.; Li, F.; He, X.; Zhang, Y.; Li, L. (Pergamon, 2018)
© 2018 Elsevier Ltd Proxies based on glycerol dialkyl glycerol tetraether (GDGT) lipids in surface sediments have been successfully used to reconstruct sea surface temperature (SST), mean annual air temperature (MAAT), and soil pH in the East China Sea and its adjacent ocean margins. In this study, two cores from the Zhejiang–Fujian coastal mud area (ZFCMA) were studied in detail to investigate temporal changes in the source and distribution of tetraether lipids in the area, and the implications of such data for paleoclimate change. The results indicate that isoprenoid GDGTs (isoGDGTs) in the ZFCMA were derived mainly from Thaumarchaeota, with a minor contribution from in situ and allochthonous methanogenic archaea in upwelling areas, whereas branched GDGTs (brGDGTs) originated mainly from terrigenous bacteria and in situ organisms. However, the minor methanogen-derived and allochthonous isoGDGTs were considered to have had no effect on inferred SSTs in this study. The presence of brGDGTs produced in situ might corrupt the relationship between the methylation index of branched tetraethers or the cyclization index of branched tetraethers (MBT/CBT) and MAAT or pH, particularly in hypoxic areas. However, #ringtetra data, used here as an index to evaluate the sources of the brGDGTs, indicated that the brGDGTs buried in the sediments are predominantly derived from soil erosion. Furthermore, temporal changes in the GDGT-based proxy records indicate that climate changes and events (e.g., relating to the East Asian Monsoon, Pacific Decadal Oscillation (PDO)/Kuroshio Current (KC) intensity, and flood events), as well as anthropogenic influences (e.g., dam construction, soil conservation, fertilizer usage, and discharge of industrial waste water and domestic sewage) affect the signal in the core sediments. SSTs fluctuated over the past 160 years in the ZFCMA, with higher values in the 20th century than in the 19th century. In addition, the humidity, as inferred from the relationship between precipitation/soil water content and pH, and continental temperature in the mid–lower Yangtze River basin switched between dry–hot/dry–cool and wet–hot/wet–cool over the last 160 years. The results also indicate that PDO/KC intensity plays a key role in temperature changes and has a larger impact on terrestrial ecosystems than on ocean ecosystems in the ZFCMA and the adjacent continent.